(untitled) (SAARC Journal of Agriculture, 2018)
The experiment was conducted at Multiplication Testing Site (MLT) Trishal of on-farm research division, Bangladesh Agricultural Research Institute, Mymensingh during 2015-16 and 2016-17 to study the comparative agro-economic performance of four crops pattern for increasing cropping intensity and productivity as compared with existing farmers’ pattern. Four crops pattern (Boro-T.Aus-T.Aman-Mustard) and farmers’ existing pattern (Boro-fallow-T.Aman- fallow) as control were tested. On an average, organic matter 3.94 t ha-1and 2.60 t ha-1 were added to soil in four crops pattern and farmers existing pattern by incorporation of biomass of respective crops.. Two years average results showed that the highest rice equivalent yield (20.63 t ha-1) was obtained from four crops pattern. The highest average gross return and gross margin of the four crops pattern were obtained Tk.359570 and Tk. 170162 ha-1 which were 80 and 207 % higher over farmers’ pattern. Farmers’ practice gave the lower gross return (Tk. 199790 ha-1). The mean marginal benefit cost ratio (MBCR) was found 2.23 which indicated the superiority of four crops pattern over the farmers’ existing pattern. The marginal benefit cost ratio (MBCR) analysis also showed that inclusion of mustard and T.Aus rice in the existing pattern might be profitable and acceptable to the farmers. Nutrient uptake and balance showed that considerable amounts of N, P, K and S were removed by crops every year. However, the N, K and S balances were found negative in all cases but P balance was found positive. From the above result showed that four crops can be grown successfully one after another in sequence of the tested pattern. SAARC J. Agri., 15(2): 103-112 (2017)